Another Asia Rabindranath Tagore and Okakura Tenshin - Bharucha, Rustom 1953- (Oxford University Press, 2006)
On the works and friendship between Rabindranath Tagore, 1861-1941, Bengali and English author and Kakuz?o Okakura, 1862-1913, Japanese author with special reference to the depiction of Asia, nationalism, and civilization in their works.